Converging on a New Theoretical Foundation for Selling. (March 2018) - Hartmann, Nathaniel N.; Wieland, Heiko; Vargo, Stephen L.
This article demonstrates that the sales literature is converging on a systemic and institutional perspective that recognizes that selling and value creation unfold over time and are embedded in broader social systems. This convergence illustrates that selling needs a more robust theoretical foundation. To contribute to this foundation, the authors draw on institutional theory and service-dominant logic to advance a service ecosystems perspective. This perspective leads them to redefine selling in terms of the interaction between actors aimed at creating and maintaining thin crossing points—the locations at which service can be efficiently exchanged for service—through the ongoing alignment of institutional arrangements and the optimization of relationships. This definition underscores how broad sets of human actors engage in selling processes, regardless of the roles that characterize them (e.g., firm, customer, stakeholder). A service ecosystems perspective reveals (1) that selling continues to be an essential activity, (2) how broader sets of actors participate in selling processes, and (3) how this participation may be changing. It leads to novel insights and questions regarding gaining and maintaining business, managing intrafirm and broad external selling actors, and sales performance.